(3GdLjfGJ GdhQGKjI hCMcGegG aj Gdabg GdESdGej (B:s (3OQGSI ebGQfI (B/s - (3GdeMdGhj, YeGO GdOjf MeO YHO Gddgs ((3HjQhJ (B:s (3ecJHI MSf GdYUQjI ddWHGYI hGdfTQhGdJhRjY ,s, 2014)
(3aj eMGhdI dQHW Yde GdLjfGJ HGdTQjYI GdESdGejI jbOe GdHGMK YeGO GdOjf GdeMdGhj OQGSI ebGQfI Mhd (B"(3GdLjfGJ GdhQGKjI hCMcGegG aj Gdabg GdESdGej(B" (3HgOa GSJcTGa GdQCj GdTQYj GdeSJfO Edi GdbQBf GdcQje hGdSfI GdfHhjI GdeWgQI aj CbhGd hGLJgGOGJ GdYdeGA aj eSGFd gGeI eKd GdESJfSGN Ch GdJYOjd GdhQGKj aj eYGdLI GdCeQGV, Ch EKHGJ GdfSH hecGaMI GdLQjeI hGdHUeI GdhQGKjI heOi eTQhYjI GSJNOGegG aj GdfSH hGdLfGjI hZjQgG ef eSGFd(B. (3dGLd Pdc bSe GdHGMK OQGSJg Edi JegjO hHGHjf LGA GdJegjO HYfhGf (B"(3JegjO GdESdGe hYde GdhQGKI(B" (3hjVe KdGKI eHGMK (B: 1-(3GdESdGe hGdEYLGR GdYdej, (B2-(3GdESdGe hGdYdhe GdWHjI, (B3-(3fUhU TQYjI OGdI Ydi Yde GdhQGKI(B. (3jdj Pdc GdHGH GdChd hLGA HYfhGf(B: "(3eaghe GdLjfGJ heLGdGJgG(B" (3hjVe aUdGf (B: (3jHMK GdChd aj GdLjfGJ GdhQGKjI ef MjK (B: (3GdJYQja GddZhj hGdEUWdGMj HGdEVGaI Edi eTQhY (B"(3GdLjfhe GdHTQj(B". (3CeG GdaUd GdKGfj ajHMK aj eLGdGJ JWHjb GdLjfGJ GdhQGKjI ef MjK GdYdGL hGdaMU hGdfSH hEKHGJ GdghjI hcTa GdLQjeI hZjQgG(B. (3CeG GdHGH GdKGfj aLGA HYfhGf (B"(3CMcGe GdLjfGJ GdhQGKjI(B" (3hjVe CQHYI aUhd JJfGhd HGdMOjK GdYdGL GdLjfj(B: (3eTQhYjJg, Mceg, GNJjGQ LfS GdLfjf, Mce GKHGJ GdfSH hGdghjI HGdJMdjd GdLjfj, Mce aMU GdLjfGJ bHd GdRhGL hHYOg hMce GLgGV GdLfjf GdeThg, hMce EKHGJ GdLQjeI HGdJMdjd GdLjfj, hMce GdSdGM GdLjfj (B((3GdHjhdhLj(B). (3hCNjQG NGJeI JVefJ HjGf HYV GdCMcGe GdTQYjI aj GdehGVjY GdJj JeJ OQGSJgG aj gPG GdcJGH(B. s
(3HHdjhLQGajI (B: (3UaMI (B251-271.s
Keywords: (3GdESdGe hGdhQGKIs -- (3GdgfOSI GdhQGKjIs